A new species of Hymenodictyon (Rubiaceae, Cinchonoideae) from Namibia - Swanepoel, Wessel; van Jaarsveld, Ernst J. (Phytotaxa, 2020)
Hymenodictyon kaokoensis, here described as a new species, has a restricted range and is only known from the mountains along the Kunene River in the Kaokoveld Centre of Endemism, northwestern Namibia. It is represented by shrubs or small trees growing in rocky places, on mountain slopes and river valleys. Diagnostic characters for H. kaokoensis include the thickset semi-succulent older stems, echinate (scabrid when dry) leaves that turn stramineous before falling, simple racemose, erect inflorescences, and ellipsoid fruits with round or elongated prominent lenticels. A comparison of some of the more prominent morphological features to differentiate between H. kaokoensis and its possible nearest relatives, H. floribundum and H. parvifolium, are provided. Based on IUCN Red List categories and criteria, a conservation assessment of Vulnerable (VU D1 & D2) is recommended for the new species.